Circadian rhythm and profile in patients with juvenile myoclonic epilepsy and temporal lobe epilepsy - Aya Fukuda; Mateus P. Funari; Paula T. Fernandes; Carlos Mantovani Guerreiro; Li Min Li (Arquivos de Neuro-Psiquiatria)
Objective This study intended to compare the circadian rhythm and circadian profile between patients with juvenile myoclonic epilepsy (JME) and patients with temporal lobe epilepsy (TLE). Method We enrolled 16 patients with JME and 37 patients with TLE from the Outpatient Clinic of UNICAMP. We applied a questionnaire about sleep-wake cycle and circadian profile. Results Fourteen (87%) out of 16 patients with JME, and 22 out of 37 (59%) patients with TLE reported that they would sleep after seizure (p < 0.05). Three (19%) patients with JME, and 17 (46%) reported to be in better state before 10:00 AM (p < 0.05). Conclusion There is no clear distinct profile and circadian pattern in patients with JME in comparison to TLE patients. However, our data suggest that most JME patients do not feel in better shape early in the day.